Application of New Energy Technologies in Marine Ports of China - Wu Jing; Yang Jiaqi; Yi Qiuyu (中国工程科学, 2024)
Promoting the application of new energy technologies in marine ports is an important way to realize the carbon peaking and carbon neutrality goals and achieve the sustainable development of ports in China. This study summarizes the current situation and trends of energy consumption in marine ports of China and analyzes the basic attributes of the application of new energy technologies in marine ports from three dimensions: economical efficiency, demand, and maturity; it involves ffshore wind power, photovoltaic  power generation, hydrogen energy, tidal energy, and biomass energy. Factors that constrain the application of new energy technologies in China’s marine ports are further discussed from three aspects: technology, economical efficiency, and technological policy. Our research indicates that the mismatch between the development level and application needs of new energy technologies, lack of centralized technology-developmentplatforms, inadequate profit models, and imperfect standards and policies collectively constrain the application of new energy sources in marine ports of China. Therefore, we propose the following suggestions: (1) establishing a collaborative research and development system for key core technologies to overcome technical difficulties and reduce application costs, (2) issuing guidance on multi-energy integration networks for ports to establish a multi-energy-complementary energy supply system, (3) optimizing the incentive mechanism for the application of new energy technologies in ports to enhance the enthusiasm of ports to apply new energy sources, and (3) improving the standards and norms for renewable energy application in ports to build a novel energy-storage supporting mechanism.